Propuesta de desarrollo turístico en la comunidad de pueblo nuevo para mejorar la oferta de servicios de playa rosada - Jarrín Sobenis, Paola (2010)
Sustainable Tourism Development in a destination responds to the needs of tourists and host regions (host community), at the same time this protects and enhancing the opportunities of the future. It is focused on the management of all resources in a sustainable manner, to meet all the economic, social and aesthetic needs, while respecting the cultural integrity, essential ecological processes, biological diversity and support systems of life. Pueblo Nuevo is a place that has warm people, with a unique flora and fauna, a natural resource and preserved as virgin as Playa Rosada and an important strategic position, allows this project to be a real competitive advantage, which it has become one positive proposal and Pro-improving throughout the area in general. To achieve all this, Studies were done such as SWOT and carrying capacity in addition to environmental impacts, market strategies, marketing management and ultimately financial, they have shown that this Action Plan for Pueblo Nuevo is effective, profitable and sustainable . All this to demonstrate to a community that with a sustainable development of resources, they can achieve socio-economic, culture and tourism growth, allowing to show the world how wonderful it is Pueblo Nuevo and Playa Rosada and at the same time to leave this treasure for future generations